Adopsi Media Sosial, Orientasi Halal, dan Kebijakan Pemerintah: Dampaknya terhadap Kinerja Bisnis UMKM Makanan dan Minuman di Indonesia - Franky Okto Bernando; Erick Lauren Ray (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study investigates the influence of social media adoption and halal orientation on the business performance of micro, small, and medium enterprises (MSMEs) in Indonesia’s food and beverage (F&B) sector. It also examines the moderating role of government policy in the relationship between halal orientation and business performance. Previous studies have emphasised the strategic importance of social media in enhancing MSME competitiveness, especially amid increasing digitalisation in Indonesia. Data were collected from 372 MSMEs in Jakarta, Indonesia, using purposive sampling based on the Krejcie and Morgan sample size guidelines. Partial least squares structural equation modeling (PLS-SEM) was employed to analyze the data. The results show that government policy significantly moderates the positive effect of halal orientation on business performance, highlighting the critical role of institutional support. This study addresses a gap in the literature concerning the interaction between religious value alignment, digital tool adoption, and external policy support. Nevertheless, the findings are context-specific and may not be generalizable beyond Jakarta. Future research should refine construct measurements related to social media adoption, entrepreneurial orientation, and government support using validated reflective indicators to enhance reliability and broader applicability.